Ruthenium-cyclopentadienyl bipyridine-biotin based compounds: Synthesis and biological effect - Corte-Real, Leonor (2019)
Prospective anticancer metallodrugs should consider target-specific components in their design in order to overcome the limitations of the current chemotherapeutics. The inclusion of vitamins, which receptors are overexpressed in many cancer cell lines, has proven to be a valid strategy. Therefore, in this paper we report the synthesis and characterization of a set of new compounds [Ru(eta(5)-C5H5)(P(C6H4R)(3))(4,4'-R'-2,2'-bpy)](+) (R = F and R' = H, 3; R = F and R' = biotin, 4; R = OCH3 and R' = H, 5; R = OCH3 and R' = biotin, 6), inspired by the exceptional good results recently obtained for the analogue bearing a triphenylphosphane ligand. The precursors for these syntheses were also described following modified literature procedures, [Ru(eta(5)-C5H3)(P(C6H4R)(3))(2)Cl], where R is -F (1) or -OCH3 (2). The structure of all compounds is fully supported by spectroscopic and analytical techniques and by X-ray diffraction studies for compounds 2, 3, and 5. All cationic compounds are cytotoxic in the two breast cancer cell lines tested, MCF7 and MDA-MB-231, and much better than cisplatin under the same experimental conditions. The cytotoxicity of the biotinylated compounds seems to be related with the Ru uptake by the cells expressing biotin receptors, indicating a potential mediated uptake. Indeed, a biotin-avidin study confirmed that the attachment of biotin to the organometallic fragment still allows biotin recognition by the protein. Therefore, the biotinylated compounds might be potent anticancer drugs as they show cytotoxic effect in breast cancer cells at low dose dependent on the compounds' uptake, induce cell death by apoptosis and inhibit the colony formation of cancer cells causing also less severe side effects in zebrafish.